2017
DOI: 10.2147/dddt.s139804
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids from Rhizoma Drynariae (Gusuibu) for treating osteoporotic fractures: implication in clinical practice

Abstract: This systematic review was performed to determine the clinical efficacy and safety of total flavonoids from Rhizoma Drynariae (TFRD) for osteoporotic fractures and to provide clear evidence for clinical practice. Eight databases were searched to identify relevant randomized controlled trials (RCTs) until December 2016. Six RCTs involving 846 patients were included. The primary outcomes included fracture recurrence and death. Meta-analysis showed that both the combination therapy and TFRD alone were better than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…Recently, plant-derived phytochemicals have received attention for their ability to induce osteoblast and osteoclast activity. Phytochemicals with promising therapeutic potential for osteoporosis include isoflavones, stilbenes and flavonoids (7). Icariin (ICA) is a major active flavonoid glycoside extracted from the Chinese herbal medicinal plant Epimedii, and it acts as a phytoestrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, plant-derived phytochemicals have received attention for their ability to induce osteoblast and osteoclast activity. Phytochemicals with promising therapeutic potential for osteoporosis include isoflavones, stilbenes and flavonoids (7). Icariin (ICA) is a major active flavonoid glycoside extracted from the Chinese herbal medicinal plant Epimedii, and it acts as a phytoestrogen.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo research also indicated that administration of TFRD significantly increased the BMD and mechanical strength and prevented bone loss induced by hindlimb unloading in rats ( Song et al., 2017 ). Furthermore, clinical practice have proved that TFRD has therapeutic effect on osteoporotic fractures by improving BMD ( Zhang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TFRD can effectively regulate osteogenesis and osteoclastrelated pathways [12]. RUNX2 is a transcription factor that belongs to the Runx family, and has been shown to be essential for osteoblast differentiation and bone formation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Total flavonoids from Rhizoma Drynariae (TFRD), a Chinese herbal product extracted from the dried root of Rhizoma Drynariae, has been developed into a postmarketing Chinese medicine called Qianggu capsule [11]. TFRD has shown good therapeutic effects on osteoporosis in human and animal models [12]. The active monomer composition of TFRD include naringin, naringenin, and neoeriocitrin [13].…”
mentioning
confidence: 99%